PERAN EMOSI POSITIF DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MENURUT PRESPEKTIF NEUROSAINS - Amal, Muhammad Muchlasul (Prosiding University Research Colloquium, 2024)
Emotions are a person's ability to recognize their own personality and others. During teaching and learning activities, students often involve their emotions in learning Islamic Religious Education (PAI). This is a normal thing because after all emotions have been natural in humans since birth. By using the literature review method, researchers want to explore how the role of positive emotions in PAI learning from a neuroscience perspective. The data analysis techniques that researchers used in this study were in the form of data collection, data reduction, and conclusions. The data sources that researchers use are articles that researchers get from national journals. The results of this study revealed that positive emotions have an important role for PAI learning. Positive emotions can be cultivated in students who are influenced by teachers such as making teaching and learning conditions pleasant. Emotions become a generator of one's energy, if a student has a lot of positive emotions in him then he will easily understand the material given by the teacher. The development of emotional intelligence in Islamic Religious Education (PAI) learning can be done with a fasting approach. Educators can direct elementary school children to do half-day fasting, while the application at the junior and senior high school levels can be done with sunnah fasts such as Monday, Thursday, Ayyamul Bidh, or Daud.